Evaluation of autologous bone marrow in wound healing in animal model: a possible application of autologous stem cells - Akela, Ashok (Int Wound J, 2011)
A study was conducted to evaluate the potential of autologous bone marrow‐derived cells in comparison with buffy coat of autologous blood for rapid cutaneous wound healing in rabbit model. Three square full‐thickness skin excisional wounds were created in 15 selected experimental animals (rabbit) divided randomly into three groups. The wound was treated with autologous bone marrow cells in plasma (group 1), buffy coat of blood in plasma (group 2) and autologous plasma as control (group 3). Wounds were observed for 30 days for granulation tissue formation, biochemical, histomorphological and histochemical evaluation. In this study, granulation tissue appeared significantly lesser in wounds of group 3 animals followed by group 2 and 1 animals. Neovascularisation, granulation tissue formation, denser, thicker and better arranged collagen fibres, reticulin fibres and elastin fibres formation was more in group 1 as compared with other groups. It was concluded that the application of bone marrow‐derived nucleated cells into the wound margins resulted in early and significantly faster rate of complete healing as compared with buffy coat of autologous blood and autologous plasma (control). This approach may be beneficial in various surface wounds that heal at a slower rate and recommended for healing of various complicated wound in future.